AKTUALISASI BISNIS DAN PEMBIAYAAN BERLABEL SYARIAH - Itmam, Shohibul (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2019)
This paper describes a business and financing labeled sharia that is currently reaping controversy in its actualization. This business practice and financing labeled sharia is different from conventional banking or financial institutions. Sharia labeled business practices and financing were initially present as a choice and solution for Muslims who want to avoid the practice of banks or conventional financial institutions that use the ribawi system which can then be an option for other Muslims. The focus of the writing is to question the actualization and existence of sharia-labeled institutions whether they are correct in substance and reflect sharia. The results of the writing are that the implementation of sharia-labeled businesses such as sharia financial institutions (LKS) still exists in substance practices so that business stakeholders are obliged to be sharia-responsible to not only practice usury-free LKS but must also be free from elements of the Shariah like gambling, speculation and so on. Islam commands to stay away from these things because it is considered as doing wrongdoing or damage. Sharia-labeled businesses and financing that are not yet appropriate are demanded not only purely business which aims to make profits as high as high by putting aside the substance of sharia but also must have the principle of mashlahah for stakeholders. Sharia business and labeling in order to remain in sharia principles whose operations are a shared responsibility between managers and state institutions appointed to carry out sharia-labeled business and financing processes and procedures in the right and correct corridors and do not engineer sharia which is merely a figment of impersonation sharia.